2008
DOI: 10.1080/00324720801955206
|View full text |Cite
|
Sign up to set email alerts
|

The demographic impact of Partition in the Punjab in 1947

Abstract: We use data from the 1931, 1941, and 1951 censuses of India and the 1951 census of Pakistan to examine the demographic consequences of Partition in the Punjab in 1947. Had growth rates for the period 1931-41 for the Punjab as a whole continued to 1951, the population of the Punjab would have been 2.9 million larger than that recorded in 1951. Population losses from migration and mortality above age 20 were approximately 2.7 million greater between 1941 and 1951 than would have been predicted by loss rates betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…The aim of the present research is thus to show that what Hill et al (2005) have concluded may hold true for the whole of Bengal, while on a micro-level, if one telescopes down to an individual border district like Nadia, one can identify significant exceptions. Moreover, with regard to religious composition, too, Nadia has some startling facts to reveal, as a direct outcome of the interplay of immigration and emigration.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The aim of the present research is thus to show that what Hill et al (2005) have concluded may hold true for the whole of Bengal, while on a micro-level, if one telescopes down to an individual border district like Nadia, one can identify significant exceptions. Moreover, with regard to religious composition, too, Nadia has some startling facts to reveal, as a direct outcome of the interplay of immigration and emigration.…”
Section: Introductionmentioning
confidence: 88%
“…Hill et al (2005) take into account the data over the census decades of 1931, 1941 and 1951, both for West Bengal and East Pakistan, to examine the local changes in population growth rates. Their conclusion is that Bengal, between 1941 and 1951, witnessed a less dramatic homogenisation of population in religious terms as compared to Punjab and a lesser growth rate as compared to the previous decade of 1931-41.…”
Section: Introductionmentioning
confidence: 99%
“…This reworked demographics across the province: in 1941, before partition, the Punjab was about 28 percent Hindu, 13 percent Sikh, and 56 percent Muslim, with the remaining population coming from Christian and other religious communities; by 1951, in parts of Punjab that were now part of Pakistan, the Hindu and Sikh populations fell to less than 1 percent, while the number of Muslims rose to at least 94 percent in each district and Christians became the largest non‐Muslim community in the province (Hill et al. 2008, 165).…”
Section: Caste Class and Religion In Urban Pakistanmentioning
confidence: 99%
“…On a broad scale, the migration brought about demographic changes, altering sex ratios, occupational structures, and literacy rates in Pakistan and India (Bharadwaj et al, 2008a). Mortality due to the migration was high (Hill et al, 2006). However, there is little empirical evidence on the economic impacts of the partition.…”
Section: Introductionmentioning
confidence: 99%